Piloter la fertilisation du palmier à huile - Dubos, Bernard (éditions Quae, 2020)
This guide designs fertilization schemes for oil palm plantations. It explains in clear language how to develop a fertilization scheme tailored to individual plantations taking the specific characteristics of each site into account. It contains numerous examples from trials conducted in different types of soils, climates and plant material in Africa and Latin America.